Educational Challenge of Health Information Systems’ Interoperability - Blobel, B. G. M. E. (Methods of Information in Medicine, 2007)
Objectives: As health care develops from an organization-centered via service-centered (disease management) towards a person-centered system (favored homecare, patient monitoring, body area networks), information systems involved have to be semantically interoperable, process-related, decision-supportive, context-sensitive, user-oriented, and trustworthy.Methods: The aforementioned paradigm shift requires highly flexible solutions based on knowledge concepts, provided by a service-oriented and model-driven approach.Results: Information systems’ design, implementation and maintenance have to be realized based on formal grammar. This is true for all considered aspects and views of the system and its components, using metalanguages and reflecting all domains touched.Conclusions: For meeting the challenge, involvement of, and close collaboration between, experts from different domains as well as knowledge and tooling regarding formal modeling and model interchange are required.
Keywords: Health information systems; formal models; meta-languages; education